2013
DOI: 10.1021/bm401433b
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Multifunctional Silk Fibroin and Hydrotalcite Nanocomposites: A Synergic Effect of the Components

Abstract: Novel hybrid functional materials are formed by combining hydrotalcite-like compounds and silk fibroin (SF-HTlc) via an environmental friendly aqueous process. The nanocomposites can be prepared with different weight ratio of the constituting components and preserve the conformational properties of the silk protein and the lamellar structure of hydrotalcites. Optical microscopy, scanning electron microscopy, and atomic force microscopy analyses show a good dispersion degree of the inorganic nanoparticles into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 75 publications
0
30
0
Order By: Relevance
“…[75][76][77] The structure of films is closely related to the rates of evaporation and the withdrawal speed of the substrate, 78 and, the film with a smaller thickness is achieved by a slower withdrawal speed. [82][83][84][85] Therefore, we will concentrate on the applications of luminescent films in chemosensors by the drop-casting technique. [82][83][84][85] Therefore, we will concentrate on the applications of luminescent films in chemosensors by the drop-casting technique.…”
Section: Chao Lumentioning
confidence: 99%
“…[75][76][77] The structure of films is closely related to the rates of evaporation and the withdrawal speed of the substrate, 78 and, the film with a smaller thickness is achieved by a slower withdrawal speed. [82][83][84][85] Therefore, we will concentrate on the applications of luminescent films in chemosensors by the drop-casting technique. [82][83][84][85] Therefore, we will concentrate on the applications of luminescent films in chemosensors by the drop-casting technique.…”
Section: Chao Lumentioning
confidence: 99%
“…In this regard, among different SF‐based biomaterials forms, SF films have shown promising results in vitro and in vivo . Indeed, it has been shown that the use of silk films could match the need of mechanical and trophic support in regenerative scaffolds by means of nanostructuring, topographic functionalization of SF with bioactive/trophic molecules, or doping the SF film matrix for controlled release of stem cells, drugs and growth factors . In this context, several processes have been reported to functionalize SF with doping molecules, growth factors and/or chemicals or nanoparticles …”
Section: Introductionmentioning
confidence: 99%
“…SF-T3-APTES films were prepared in according to the literature 11 . Specifically, note aliquots of silk solution and SEC eluted SF-APTES-T3 fractions were dropped on a support/mold of polydimethylsiloxane (PDMS), left dried, and piled off from the PDMS substrate in order to obtain free-standing composite films.…”
Section: Sf Dye Doping Counter-experimentsmentioning
confidence: 99%
“…Chemical approaches so far proposed for modifying silk fibroin rely on both covalent bonding [6][7][8][9] and non covalent interactions. [10][11][12] SF contains serine, threonine, asparticglutamic acid, and tyrosine that can undergo supramolecular interactions and that can all be targeted and modified exploiting known organic synthesis procedures. Among them, Murphy et al recently demonstrated the possibility of diazonium coupling on tyrosine residues, as efficient approach for introducing new reactive functionalities or to enrich SF of naturally present chemical groups.…”
Section: Introductionmentioning
confidence: 99%